3+8(x)=3(2)(x)-1

Simple and best practice solution for 3+8(x)=3(2)(x)-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3+8(x)=3(2)(x)-1 equation:


Simplifying
3 + 8(x) = 3(2)(x) + -1

Multiply 3 * 2
3 + 8x = 6x + -1

Reorder the terms:
3 + 8x = -1 + 6x

Solving
3 + 8x = -1 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
3 + 8x + -6x = -1 + 6x + -6x

Combine like terms: 8x + -6x = 2x
3 + 2x = -1 + 6x + -6x

Combine like terms: 6x + -6x = 0
3 + 2x = -1 + 0
3 + 2x = -1

Add '-3' to each side of the equation.
3 + -3 + 2x = -1 + -3

Combine like terms: 3 + -3 = 0
0 + 2x = -1 + -3
2x = -1 + -3

Combine like terms: -1 + -3 = -4
2x = -4

Divide each side by '2'.
x = -2

Simplifying
x = -2

See similar equations:

| 150=-16t^2+118t+3 | | 1/2a-4=3-1/4 | | 7+.2(x-1)=5+.3(x-1) | | 4/5×5 | | (16-9i)-(2-9i)= | | 3/5x-1/10x=x-15/2 | | 9p+4+3p= | | 2y-6.3=y+13 | | 28+28+28= | | 5/8*2/5 | | 5(t+3)= | | 12-2x=8(x)+4 | | 40+40+40= | | 492x+10=5x+3x+9 | | 3n+4n-5+3= | | -4y-2=3y-4 | | 2y+40=7y | | -216=-9g | | 2(9y-7)=14 | | c-3=12 | | r=2xy-3p | | 45-6x=x+171 | | 0.6+k=1.67 | | X*4x=12.6 | | 1/3÷3 | | (4x+2)+(7x+4)+(3x+20)=180 | | 2(2x+8)=2(4x+8) | | D=125.145h | | 9x-6x+1=9x+1-x | | 8b+8b+4b=-12 | | 2-2x=2x+2 | | H=125.145d |

Equations solver categories